2023
DOI: 10.1002/adma.202306996
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Guided Crystallization of Xanthine Derivatives for Optical Metamaterial Applications

Angelica Niazov‐Elkan,
Margarita Shepelenko,
Lotem Alus
et al.

Abstract: Numerous bio‐organisms employ template‐assisted crystallization of molecular solids to yield crystal morphologies with unique optical properties that are difficult to reproduce synthetically. Here, a facile procedure is presented to deposit bio‐inspired birefringent crystals of xanthine derivatives on a template of single‐crystal quartz. Crystalline sheets that are several millimeters in length, several hundred micrometers in width, and 300–600 nm thick, are obtained. The crystal sheets are characterized with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In order to assign the birefringence axes, the crystallographic axes of the single crystal are characterized by the in-plane and out-of-plane XRD measurements, as schematically depicted in Figure a. , The out-of-plane XRD scan revealed that the (114) lattice planes are perpendicular to the elongated surface of the rod (Figure b) suggesting a preferred ⟨114⟩ growth direction along the elongated surface of the rod (Figure c). The in-plane XRD scan reveals that (012) lattice planes are parallel to the elongated surface of the rod (Figure d).…”
mentioning
confidence: 99%
“…In order to assign the birefringence axes, the crystallographic axes of the single crystal are characterized by the in-plane and out-of-plane XRD measurements, as schematically depicted in Figure a. , The out-of-plane XRD scan revealed that the (114) lattice planes are perpendicular to the elongated surface of the rod (Figure b) suggesting a preferred ⟨114⟩ growth direction along the elongated surface of the rod (Figure c). The in-plane XRD scan reveals that (012) lattice planes are parallel to the elongated surface of the rod (Figure d).…”
mentioning
confidence: 99%